HUBUNGAN PRESTASI PADA MATA KULIAH MOTOR, KELISTRIKAN DAN SISTEM PEMINDAH TENAGA DENGAN KEMAMPUAN MENDIAGNOSA KERUSAKAN SEPEDA MOTOR MAHASISWA PENDIDIKAN TEKNIK OTOMOTIF FAKULTAS TEKNIK UNM - Muhammad Fadil Syafiuddin; Muhammad Yahya; Anas Arfandi (UNM Journal of Technology and Vocational, 2024)
This correlation study aims to determine: (1) description of learning achievement in the subject of Motor (Engine), Automotive Electrical and Power Train Systems as well as description of the ability to diagnose damage to motorcycles of students of the Automotive Engineering Education Study Program, Faculty of Engineering, Makassar State University; (2) the relationship between learning achievement in the Motor (Engine) course and the ability to diagnose damage to motorbikes of PTO FT UNM students, (3) the relationship between learning achievement in the Automotive Electrical subject and the ability to diagnose damage to motorbikes of PTO FT UNM students, (4) the relationship between learning achievement in the Power Train Systems course and the ability to diagnose damage to motorbikes of PTO FT UNM students, (5) the joint relationship between the Motor (Engine) courses, Automotive Electrical and Power Train Systems with the ability to diagnose damage to motorcycle PTO FT UNM students. A sample of 110 people was drawn by proportional random sampling from a population of 152 people. The results showed (1) the learning achievement of students majoring in PTO FT UNM in the subject of Motor, Automotive Electrical and Power Train Systems was classified as "high" while the ability to diagnose damage to motorcycles was "quite high" (2) there was a positive and very strong relationship between learning achievement in the Motor (Engine) course and the ability to diagnose damage to motorcycles for students of the PTO FT UNM Study Program, (3) there is a positive and "quite strong" relationship between learning achievement in the Electrical subject Automotive with the ability to diagnose damage to motorcycles of students of the PTO FT UNM Study Program, (4) there is a positive but relatively “low” relationship between learning achievement in the Power Train Systems course and the ability to diagnose damage to motorcycles of Study Program students PTO FT UNM, (5) there is a jointly positive and "very strong" relationship between learning achievement in the subjects Motor (Engine), Automotive Electrical and Power Train Systems with the ability to diagnose damage to motorcycles for students of the PTO FT UNM Study Program